PERPAJAKAN DAN MANAJEMEN LABA: PERAN KEPEMILIKAN INSTITUSIONAL - Adillah Abir Syofnita; Elfiswandi Elfiswandi; Ramdani Bayu Putra; Hasmaynelis Fitri (Jurnal Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of deferred tax expense,tax planning and managerial ownership of earnings management with institutional ownership as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The sample in this study used a purposive sampling method, so that there were 58 companies that would be sampled for 5 consecutive years so that a total of 290 companies were observed. This research usesmoderated regression analysis (MRA) with the help of the Eviews 10 program. The results of testing the hypothesis state that deferred tax expense andtax planning has a positive and significant effect on earnings management, while institutional ownership has no significant effect on earnings management, then institutional ownership is able to moderate the relationship between deferred tax expense andtax planning on earnings management while institutional ownership is not able to moderate the relationship between managerial ownership on earnings management.